NON – ENGLISH DEPARTMENT STUDENTS’ PERCEPTION OF LEARNING ENGLISH - Resa Andiyani; Tanto Setia Muljanto; Muhamad Taufik Hidayat (English Education and Applied Linguistics Journal (EEAL Journal), 2020)
This study aimed to investigate the Non-English department students’ perception toward learning English in Faculty of Science and Technology. This study employed a qualitative research in which using ex-post facto design. The participant of this study were 10 out of 150 students of mathematic program. The data were collected by using questionnaires and in- depth interview. The items for the questionnaire were developed from the previous research Abidin (2012) which were found appropriate to be used. The data were then analyzed using three aspect of perception i.e., cognitive, behavioral, and emotional. There was a statistically change between positive and negative respond from the students. They were thought English was important to know and learn English because English opens up the widest possible job and employment opportunities in many countries and markets. Working knowledge of the English language can create many opportunities not only in regions but also in international markets and they also tried to improve their English in some ways although the participants find difficulties. They found difficult in learning English in the four basic skill of English. They felt difficult when they have to read math symbols in English